2006
DOI: 10.1007/s00259-006-0119-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of wire localisation for non-palpable breast lesions on visualisation of the sentinel node

Abstract: This study shows that guide wire localisation prior to the sentinel node procedure negatively influences visualisation of the sentinel node.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…Wire migration and displacement and interference with the SN procedure are well known [4,6,29]. Unlike the wire guided procedures, there are no serious complications described so far in the ROLL procedure apart from misplacement of the radiotracer which occurred in 1 patient (2.4%) in the present study where no tumor was found on histopathology.…”
Section: Discussioncontrasting
confidence: 66%
“…Wire migration and displacement and interference with the SN procedure are well known [4,6,29]. Unlike the wire guided procedures, there are no serious complications described so far in the ROLL procedure apart from misplacement of the radiotracer which occurred in 1 patient (2.4%) in the present study where no tumor was found on histopathology.…”
Section: Discussioncontrasting
confidence: 66%
“…In both protocols patients had a guide wire in place during injection of the radiotracer. It has been suggested that the presence of a guide wire can disturb the regular draining pattern and radiotracer can leak past the guide wire [ 2 ]. The numbers of guide wires in place during injection of radiotracer were comparable between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore a guide wire is usually placed preoperatively in order to localize the tumour. It is suggested that a guide wire placed intra- or peritumorally could disturb the lymph drainage pattern and thereby decrease the success rate of the SLNB [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although two different studies reported in univariate analyses a signi cant correlation between tumor size > 20 mm and SLN nonvisualization lymphoscintigraphy in breast cancer patients, Hellingman et al showed in a multivariable model an equal correlation between tumor size and SLN nonvisualization(6,7,13). Despite this fact, we and the vast majority of other research groups were unable to nd any signi cant effect of tumor size on SLN nonvisualization(2)(3)(4)(5)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 56%